THE EFFECT OF QUALITY PRODUCTS TO THE CUSTOMER’S DECISION IN USING PGN GAS IN BATAM SOCIETY WITH THE SERVICE QUALITY AS MODERATION VARIABLE - Hendri Herman; Vargo Christian L. Tobing (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
This research has the purpose of knowing the role of product quality to consumer decisions in the use of PGN Gas with service quality as a moderation variable. The respondents in this study were households who had used PGN gas with a total of 98 respondents. The data in this study was obtained by distributing questionnaires to respondents. The data that has been collected will be tabulated then processed by using the SPSS data processing program. The results of the study, it is known that the quality of the product has a significant influence on consumer decisions. However, the quality of service is not able to moderate the effect of product quality on consumer decisions in the use of PGN gas.